2020
DOI: 10.3389/fphys.2019.01610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modest Hypoxia and Exercise on Cardiac Function, Sleep-Activity, Negative Geotaxis Behavior of Aged Female Drosophila

Abstract: Mild normobaric hypoxia (NH) and modest exercise have multiple beneficial effects on health, but the changes in physiological function induced by NH and/or exercise remain unclear. The purpose of this investigation was to examine the specific effects of NH and/or exercise on cardiac function and myocardial structure and behavior including sleep-activity and negative geotaxis in aged Drosophila. We also assessed the survival rate of flies after hypoxia and/or exercise. One-thousand wild-type w 1118 virgin femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 84 publications
2
13
0
Order By: Relevance
“…Our previous studies demonstrated that prolonged fatigue exercise increases sleep stability and improves sleep quality in aging Drosophila [ 46 , 47 , 48 ], but the regulatory mechanisms remain unclear. Based on the aging change characteristics of sleep–wake behavior, two exercise protocols were designed in this study: exercise starting from young adulthood to middle age (E1), and exercise starting from middle age to old age (E2) ( Figure 5 A), which aimed to investigate the effect of endurance exercise starting at different ages on age-dependent sleep–wake behavior decline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that prolonged fatigue exercise increases sleep stability and improves sleep quality in aging Drosophila [ 46 , 47 , 48 ], but the regulatory mechanisms remain unclear. Based on the aging change characteristics of sleep–wake behavior, two exercise protocols were designed in this study: exercise starting from young adulthood to middle age (E1), and exercise starting from middle age to old age (E2) ( Figure 5 A), which aimed to investigate the effect of endurance exercise starting at different ages on age-dependent sleep–wake behavior decline.…”
Section: Resultsmentioning
confidence: 99%
“…In the E1 exercise protocol, we found that endurance exercise increased sleep time in mir-283 SP /+ flies ( Figure 5 C,F). Although activity behavior decreased ( Figure 5 E,J), the activity frequency increased upon awakening ( Figure 5 K), as the activity index (the number of activities per minute) was a better indicator of health in the flies [ 22 , 23 , 48 ], indicating that exercise improved health in middle-aged Drosophila . JTK_CYCLE and CircaCompare analyses indicated that endurance exercise ameliorated age-dependent sleep cycle lengthening, allowing mir-283 SP /+ Drosophila to still maintain a 12 h circadian oscillation with an increased rhythmic amplitude of sleep, activity, and rest ( Figure 5 C–E, Table S3 ), suggesting that endurance exercise initiated in youth maintains a relatively stable sleep–wake rhythm output.…”
Section: Resultsmentioning
confidence: 99%
“…In both obese and diabetic rodent models and human subjects, myocardial steatosis is associated with functional and structural changes in the heart [ 44 , 64 ]. In addition, cardiac aging in mammals is always accompanied by disorganized and reduced myocardial fiber arrangement [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Drosophila exercise training device is designed according to Tower power and Swing boat [ 16 , 18 ]. As previously, flies were stimulated to actively walk upwards by flipping the vial for exercise [ 50 ]. In this study, the flies in the exercise group were placed in the exercise training device within 24 hours after eclosion, working out 2.5 hours a day, 5 days a week with two days off, for a total of two weeks.…”
Section: Methodsmentioning
confidence: 99%